The Nutraceutic Silybin Counteracts Excess Lipid Accumulation and Ongoing Oxidative Stress in an In Vitro Model of Non-Alcoholic Fatty Liver Disease Progression - Vecchione, Giulia; Grasselli, Elena; Cioffi, Federica; Baldini, Francesca; Oliveira, Paulo J.; Sardão, Vilma A.; Cortese, Katia; Lanni, Antonia; Voci, Adriana; Portincasa, Piero; Vergani, Laura (Frontiers in Nutrition, 2017)
Non-alcoholic fatty liver disease (NAFLD) is a major cause of liver-related morbidity and mortality. Oxidative stress and release of pro-inflammatory cytokines, such as tumor necrosis factor α (TNFα), are major consequences of hepatic lipid overload which can contribute to progression of NAFLD to non-alcoholic steatohepatitis (NASH). Also mitochondria are involved in the NAFLD pathogenesis for their role in hepatic lipid metabolism. Definitive treatments for NAFLD/NASH are lacking so far. Silybin, the extract of the milk thistle seeds, has previously shown beneficial effects in NAFLD. Sequential exposure of hepatocytes to high concentrations of fatty acids (FAs) and TNFα resulted in fat overload and oxidative stress which mimic in vitro the progression of NAFLD from simple steatosis (SS) to steatohepatitis (SH). The exposure to 50 μM silybin for 24h reduced fat accumulation in the model of NAFLD progression. The in vitro progression of NAFLD from SS to SH resulted in reduced hepatocyte viability, increased apoptosis and oxidative stress, reduction in lipid droplet size, up-regulation of IκB kinase β interacting protein (IkBip) and of adipose triglyceride lipase (ATGL) expression. The direct action of silybin on SS or SH cells and the underlying mechanisms were assessed. Beneficial action of silybin was sustained by changes in expression/activity of peroxisome proliferator-activated receptors (PPARs), and of enzymes for FA oxidation. Moreover, silybin counteracted the FA-induced mitochondrial damage by acting on complementary pathways: (i) increased the mitochondrial size and improved the mitochondrial cristae organization; (ii) stimulated mitochondrial FA oxidation; (iii) reduced basal and maximal respiration and ATP production in SH cells; (iv) stimulated ATP production in SS cells; (v) rescued the FA-induced apoptotic signals and oxidative stress in SH cells. We provide new insights about the direct protective effects of the nutraceutic silybin on hepatocytes mimicking in vitro NAFLD progression.